ACADEMIC PROCRASTINATION AMONG STUDENTS: THE INFLUENCE OF SOCIAL SUPPORT AND RESILIENCE MEDIATED BY RELIGIOUS CHARACTER - Madjid, Abd.; Sutoyo, Dian Aryogo; Shodiq, Sadam Fajar (Jurnal Cakrawala Pendidikan, 2021)
Academic procrastination among students is a serious problem with significant consequences. Social support and resilience are considered to have an important influence on students’ academic procrastination. This study aims to prove and analyze the effects of social support and resilience on students’ academic procrastination before and after mediation by religious character. Structural equation model (SEM) analysis test was used on the academic procrastination of students influenced by social support and resilience and mediated by religious character. The study population comprised 10,271 students from 9 faculties. The total sample was determined to be 797 students on the basis of Slovin’s formula. The research model analysis was conducted using a two-step approach involving measurement model analysis and SEM analysis to analyze the relationship between all latent variables in the research model. The results show that social support from family, friends, and the school can reduce the level of academic procrastination. Resilience is found to reduce and exert a significant and indirect effect on academic procrastination after mediation by religious character.